Crooked crows eaudiobook - Lawson, Elena (Boys of Briar Hall, 2021)
Unapologetically f*cked up. Heartlessly cruel. Broken beyond repair. Corvus, Rook, and Grey - The Crows. Bred in a world of gang wars, violence, and secrets, they rule the bloody town of Thorn Valley and all the people in it...too bad for me I've never been good at kissing ass or keeping quiet. Even if their savage spirits awaken something inside of me I thought was long dead, I can't break. I won't. They think they scare me, that I'll run and hide, but the joke's on them. The Crows aren't the first monsters I've faced, and they won't be the last. There are worse evils out there waiting to take their stab at Ava Jade Mason. I say let them try. I'm tired of running. Tired of holding back my darkness. Thorn Valley isn't ready for a new boogie man. Too bad I'm already here. Crooked Crows is a dark enemies-to-lovers #WhyChoose romance, meaning the main character will have more than one love interest.